USING SONGS IN THE SPEAKING CLASS: Improving Students’ Abilities in a Relaxing Way. - Dahler Dahler (Universitas Lancang Kuning, 2014)
This Classroom Action Research (CAR) aimed to find out whether students’ activities through song can be used as media for improving the students speaking skill. The participants of this study were 21 students of English department, Lancang Kuning University academic year 2012/2013. This present study conducted in two cycles, and each of the cycle had four meetings during April - Mei 2012. After analyzing the data, it was found that the activities through song improved the students’ speaking skill and influenced all indicators of speaking skill in term of accent, grammar, vocabulary, fluency, and comprehension. Furthermore, it built up the students’ confidence and participation in class. The researcher concluded that the students’ activities through song can improve the students’ speaking skill.